Quantitative study of the causal relationships among the EFQM model 2020 criteria in the Greek public sector context - Mitsiou, Dimitra; Zafiropoulos, Kostas (Journal of Business Economics and Management, 2024)
This study aims to apply the European Foundation for Quality Management (EFQM) Model 2020 in the Greek Public Sector context and investigate the causal relationships between the model’s criteria. The research uses a structured questionnaire based on the self-assessment tool and the guidelines on the concept and structure of the EFQM Model 2020, translated from English into Greek using forward-backward translation. Two focus groups and a pilot study were conducted to ensure the validity and reliability of the questionnaire. Subsequently, a large-scale quantitative research was conducted using Partial Least Square Structural Equation Modelling (PLS-SEM) to test the research hypotheses on a national sample of 177 managers from public administrative services. The study results indicate that the EFQM Model 2020 is indeed a reliable and valid framework for the study of the public sector and reveal significant relationships between the model’s criteria. The study is one of the first comprehensive investigations of the relationships between the EFQM Model 2020 criteria in Europe and, therefore, provides insights into the understanding of the model. As this research was geographically limited, the findings should be treated and generalised with caution, and further research should be conducted in different contexts.